Analisis Pengaruh Pendidikan, Sosial, dan Pengetahuan Terhadap Minat Masyarakat Menabung di Bank Syariah (Studi Kasus di Desa Jatikuwung Gondangrejo Karanganyar) - Umi Hani'in; Fitri Ernawati; Iin Emy Prastiwi; A Haris Romdhoni (JURNAL ILMIAH EDUNOMIKA, 2021)
This study was conducted to examine whether there is a significant influence on education, social factors and knowledge on people's interest in saving at Islamic banks in Banyubiru, Jatikuwung Village, Gondangrejo Karanganyar. This study aims to determine and analyze education, social factors and knowledge of interest in saving in Islamic banks. The research method used in this study is quantitative with primary data sources originating from the distribution of questionnaires in the Banyubiru Jatikuwung Gondangrejo Karanganyar hamlet community. The sampling technique is by using the slove in formula. Data analysis methods in the form of Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, F Test, t Test and Determination Test. The results of this study using the t test (partial test) showed that the knowledge variable had no significant effect on the interest in saving in Islamic banks while the education variable and social factors had a significant effect on the interest in saving in Islamic banks. The results of the F-test (simultaneous test) show that the variables of education, social factors, and knowledge have a significant influence on interest in saving in Islamic banks bank. Judging from the Adjusted R-square value of the education variable, social and knowledge factors affect the interest in saving in Islamic banks by 57%. Keywords : Interest, education, social factors and knowledge